Relación entre la condición de salud oral y su autopercepción en adultos mayores de la unidad de prestaciones sociales de essalud de la red asistencial la libertad, 2015 - Merino Carranza, Didier Alan (2016)
OBJETIVE: To determinate the relationship between oral health conditions and it’s self-perception in older adults of the Unidad de Prestaciones Sociales of Essalud of the Red Asistencial La Libertad. MATERIALS AND METHODS: The following descriptive, transversal and correlational investigation, related the older adults oral health conditions and it´s self-perception, and was made in a sample of 304 adults, all of them users of the 8 Older Adult Centers of the Red Asistencial La Libertad. RESULTS: Determining the oral health conditions and it’s self-perception in older adults, was founded that 304 older adults presented a poor oral health conditions, distributed 90.8% (276) as poor self-perception and 9.2% (28) as moderate condition. For this study the self-perception of oral health was determined by the application of GOHAI index. CONCLUSIONS: The older adult’s oral health condition is not related to its self-perception.